Chiroptical and potential in vitro anti-inflammatory properties of viniferin stereoisomers from grapevine (Vitis vinifera L.). (1st November 2022) - Buffeteau, Guillaume; Hornedo-Ortega, Ruth; Gabaston, Julien; Daugey, Nicolas; Palos-Pinto, Antonio; Thienpont, Anne; Brotin, Thierry; Mérillon, Jean-Michel; Buffeteau, Thierry; Waffo-Teguo, Pierre
Graphical abstract: Highlights: Viniferins were isolated from vine stalks using a combination of CPC and Prep. HPLC. The enantiomers of E-ε- viniferins and E-ω- viniferins were purified by chiral HPLC. NMR and VCD associated to DFT calculations establish the (7aS, 8aS) and (7a R, 8a S ) configurations for E - ε - and E - ω -viniferin. Cabernet Sauvignon grape variety provides the quasi enantiopure (+)-(7a S, 8a S )- E-ε -viniferin compound. (+)-(7a S, 8a S )- E-ε- viniferin was the most efficient compound diminishing NO and ROS. Abstract: Determination of stereochemistry and enantiomeric excess in chiral natural molecules is a research of great interest because enantiomers can exhibit different biological activities. Viniferin stilbene dimers are natural molecules present in grape berries and wine but also, in larger amount, in stalks of grapevine. Four stereoisomers of viniferin stilbene dimers (7a S, 8a S ) -E-ε- viniferin (1a ), (7a R, 8a R ) -E-ε- viniferin (1b ), (7a S, 8a R ) -E-ω- viniferin (2a ), and (7a R, 8a S ) -E-ω- viniferin (2b ) were isolated from grapevine stalks of Cabernet Sauvignon, Merlot and Sauvignon Blanc, using a combination of centrifugal partition chromatography (CPC), preparative and chiral HPLC. The structure elucidation of these molecules was achieved by NMR whereas the absolute configurations of the four stereoisomers were investigated by vibrational circular dichroism spectroscopy in combination with density functional theory (DFT) calculations. This study unambiguously established the (+) - (7a S, 8a S ) and (+) - (7a R, 8a S ) configurations for E-ε- viniferin and E-ω- viniferin, respectively. Finally, we show that Cabernet Sauvignon provided the quasi enantiopure (+) - (7a S, 8a S ) -E-ε- viniferin compound which presents the best anti-inflammatory and anti-oxidant activities.